FROM WHERE DO THE SOCIAL STUDIES IN CUBA, SPEAK US? - Gómez González, Susell (2012)
This article presents an approach to the role of the Cuban education system, with the opening of a new career in the field of Social Sciences, which shows the reflections of the postmodern context today. This is developed from the recreation room culturologic speech, even working its appearance in Cuba and its challenges, recreating some guidelines, such as: Opens a new path in Cuban social sciences and the University of Granma, the scene of professional performance of Sociocultural Studies in Cuba, which narrate encounters and misunderstandings of this new career and discipline in their professional training.